1997
DOI: 10.1088/0022-3727/30/21/010
|View full text |Cite
|
Sign up to set email alerts
|

Computation of net emission of - thermal plasmas

Abstract: Assuming local thermodynamic equilibrium (LTE), the total radiation which escapes from a - plasma is calculated in the temperature range between 5000 and 30 000 K. The evaluation of the net emission coefficient is performed by solving the radiative transfer equation in a cylindrical isothermal plasma taking into account line broadening phenomena. The radiation emission of methane depends mainly on the carbon species, whereas the presence of hydrogen in the mixture leads to a radiation decrease especially at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The methods for calculating the emission or absorption coefficients relative to these mechanisms were given in previous papers (see, e.g. [5]). The application of these methods to nitrogen and oxygen needs some basic data.…”
Section: Atomic Continuummentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for calculating the emission or absorption coefficients relative to these mechanisms were given in previous papers (see, e.g. [5]). The application of these methods to nitrogen and oxygen needs some basic data.…”
Section: Atomic Continuummentioning
confidence: 99%
“…It has been demonstrated that the use in the energy equation of a net emission coefficient (NEC) defined by Lowke [1] as the divergence of the radiative flux at the centre of an isothermal sphere, allows to compute with a satisfactory accuracy, the temperature of the hottest regions of the plasma [2]. As the maximum temperature is often higher than 10 000 K, the radiation of the hottest regions is mainly due to atomic species (neutrals and ions); in these conditions the NEC was calculated taking only into account the atomic species, even for plasmas created in molecular gases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The atomic continuum theory was thoroughly studied in the previous papers of Gleizes et al [77], Liani et al [78] and Cressault [79].…”
Section: Atomic Continuummentioning
confidence: 99%
“…The radiative intensities of argon and oxygen were taken from the literature (Miller and Ayen, 1969;Krey and Morris, 1970;Liani, 1997). Table 1 summarizes the reactions in the argonoxygen plasma.…”
Section: Thermodynamic and Transport Propertiesmentioning
confidence: 99%